Participatory methods for information society - Bonecki, Mateusz; Malitowska, Anna (Filozofia Publiczna i Edukacja Demokratyczna, 2016)
The paper provides introductory remarks to the special issue of Public Philosophy and Democratic Education dedicated to the role of participatory methods in contemporary informational society. The authors posit that in relation to classical definitions of knowledge economy, which treat knowledge as a fundamental factor of production leading to innovations in products and services, one can also acknowledge the democratizing of the innovation (technical, social, or institutional) due to increased participation of society in the process. The authors refer to information technologies which enable citizens’ participation in urban governance. They also emphasize the role of participatory-foresight methods in creating public policy based on long-term citizens-driven visions of social and economic development.